2019
DOI: 10.1177/0886260519873333
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Problems, Jealousy, and Cyber Dating Abuse Perpetration Among Men and Women: Toward a Conceptual Model

Abstract: Investigations of alcohol use in relation to cyber dating abuse (CDA) remain underdeveloped relative to alcohol-related face-to-face dating abuse research. A critical step toward advancing this area of research would include examining the applicability of alcohol-related partner abuse models to CDA perpetration. Existing models of alcohol-related partner abuse suggested that alcohol and partner abuse are more likely to co-occur in the presence of aggressogenic distal traits. We propose that this model may exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 52 publications
(106 reference statements)
0
15
3
Order By: Relevance
“…Although extant data suggests that the prevalence of past-year cyber PA perpetration is comparable across college women and men (Brem, Romero, et al, 2019), the present data revealed that women's odds of daily cyber PA perpetration were greater than men's odds. It is plausible that cyber PA perpetration is perceived as a more acceptable form of abuse among women relative to men.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Although extant data suggests that the prevalence of past-year cyber PA perpetration is comparable across college women and men (Brem, Romero, et al, 2019), the present data revealed that women's odds of daily cyber PA perpetration were greater than men's odds. It is plausible that cyber PA perpetration is perceived as a more acceptable form of abuse among women relative to men.…”
Section: Discussioncontrasting
confidence: 95%
“…With the advent and ubiquity of smartphones and social media, college couples have virtually constant access to one another thereby creating new contexts for individuals to monitor, harass, threaten, humiliate, and otherwise abuse their partners via technology, otherwise known as cyber PA (Borrajo et al, 2015; Elphinston & Noller, 2011; Leisring & Giumetti, 2014). Approximately 44% of college men and 55% of college women perpetrate at least one form of cyber PA each year which may increase their partners’ likelihood of experiencing deleterious mental health consequences (e.g., depression, suicidal ideation, and risky sexual behaviors; Brem, Romero, et al, 2019; Van Ouytsel et al, 2016; Wolford-Clevenger, Elmquist, et al, 2016; Wolford-Clevenger, Zapor, et al, 2016). Despite the prevalence and negative experiences associated with cyber PA, theory and research in this area remain underdeveloped.…”
Section: Aims and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to elucidating the longitudinal associations between cyber, psychological, and physical DA, research would benefit from clarifying theory-informed cyber DA risk factors. Alcohol use gained support as an antecedent for in-person DA (Shorey, Stuart, McNulty, & Moore, 2014; Shorey, Stuart, Moore, & McNulty, 2014), and some evidence suggested alcohol use posed a risk for cyber DA (Brem et al, 2019; Crane, Umehira, Berbary, & Easton, 2018; Singh et al, 2015; Van Ouytsel et al, 2016). Cross-sectional data revealed that alcohol use positively related to cyber DA perpetration among adult men and women (Crane et al, 2018; Singh et al, 2015).…”
Section: Cyber Da Perpetrationmentioning
confidence: 99%
“…That is, alcohol problems may increase subsequent DA perpetration for individuals with high, but not low, levels of aggressogenic dispositional traits. Brem et al (2019) recently proposed that such a model could be applied to cyber DA such that distal traits interact with alcohol problems to increase the risk of cyber DA.…”
Section: Alcohol Emotion Dysregulation and Da Perpetrationmentioning
confidence: 99%